Comparative Analyses of Euonymus Chloroplast Genomes: Genetic Structure, Screening for Loci With Suitable Polymorphism, Positive Selection Genes, and Phylogenetic Relationships Within Celastrineae - Li, Yongtan; Dong, Yan; Liu, Yichao; Yu, Xiaoyue; Yang, Minsheng; Huang, Yinran (Frontiers in Plant Science, 2021)
In this study, we assembled and annotated the chloroplast genome of the Euonymus species Euonymus fortunei, Euonymus phellomanus and Euonymus maackii, and performed a series of analyses to investigate gene structure, GC content, sequence alignment and nucleic acid diversity, with the objectives of identifying positive selection genes and understanding evolutionary relationships. The results indicated that the Euonymus chloroplast genome was 15,6860 bp-15,7611 bp in length and exhibited a typical circular tetrad structure. Similar to the majority of angiosperm chloroplast genomes, the results yielded a large single-copy region (85,826–86299 bp) and a small single-copy region (18,319–18,536 bp), separated by a pair of sequences (IRA and IRB; 26,341–26,700 bp) with the same encoding but in opposite directions. The chloroplast genome was annotated to 130–131 genes, including 85–86 protein coding genes, 37 tRNA genes, and 8 rRNA genes, with GC contents of 37.26–37.31%. The GC content was variable among regions and was highest in the IR region. The IR boundary of Euonymus happened expanding resulting that the rps19 entered into IR region and doubled completely. Such fluctuations at the border positions might be helpful in determining evolutionary relationships among Euonymus. The simple-sequence repeats (SSRs) of Euonymus species were composed primarily of single nucleotides (A)n and (T)n, and were mostly 10–12 bp in length, with an obvious A/T bias. We identified several loci with suitable polymorphism with the potential use as molecular markers for inferring the phylogeny within the genus Euonymus. Signatures of positive selection were seen in rpoB protein encoding genes. Based on data from the whole chloroplast genome, common single copy genes, and the LSC, SSC, and IR regions, we constructed an evolutionary tree of Euonymus and related species, the results of which were consistent with traditional taxonomic classifications. It showed that Euonymus fortunei sister to the Euonymus japonicus, whereby Euonymus maackii appeared as sister to Euonymus hamiltonianus. Our study provides important genetic information to support further investigations into the phylogenetic development and adaptive evolution of Euonymus species.